1996
DOI: 10.1080/00405009608631352
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Cotton Yarn Irregularity Based on the ‘AFIS’ Measurement

Abstract: This paper presents a neural network model for predicting the yarn irregularity, based on inputs of fiber property measurements with the AFIS instrument. By using a back-propagation neural network algorithm, alternative models were fitted and compared. The resulting predictions of yarn irregularity are superior to these obtained by using conventional multiplelinear regression techniques.• I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Rajamanickam et al [11], Guha et al [12] and Majumdar and Majumdar [13] have demonstrated that the prediction performance of ANN models is much better than that of classical mechanistic or regression models. Zhu and Ethridge [14] predicted the unevenness of spun yarns from advanced fiber information system (AFIS) parameters using ANN and obtained good prediction results. In a similar research, Guha [15] predicted the unevenness of ring and rotor spun yarns using ANN and found that the mean error of prediction was always less than 4 % for three different datasets.…”
Section: Introductionmentioning
confidence: 95%
“…Rajamanickam et al [11], Guha et al [12] and Majumdar and Majumdar [13] have demonstrated that the prediction performance of ANN models is much better than that of classical mechanistic or regression models. Zhu and Ethridge [14] predicted the unevenness of spun yarns from advanced fiber information system (AFIS) parameters using ANN and obtained good prediction results. In a similar research, Guha [15] predicted the unevenness of ring and rotor spun yarns using ANN and found that the mean error of prediction was always less than 4 % for three different datasets.…”
Section: Introductionmentioning
confidence: 95%
“…The advent of artificial intelligence has provided a new impetus in the research on modelling of yarn properties. Cheng and Adams [10], Ramesh, Rajamanickam and Jayaraman, [11], Zhu and Ethridge [12,13], Guha, Chattopadhyay and Jayadeva [14] and Majumdar and Majumdar [15] have successfully used the artificial neural network (ANN) and neural-fuzzy methods to predict various properties of spun yarns. The prediction accuracy of ANN has been acclaimed by most of these researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Related to this context, this paper deals with the modelling of the relationships between the structural parameters and the expected features of nonwovens. In this research work, soft computing techniques such as neural networks are implemented for modelling these relationships (Ramesh et al, 1995;Ethridge, 1996 &Sette et al, 1997;Kuo et al, 1998;Fan and Hunter, 1998;Kuo, et al 1999;Xu et al, 1999). Our major goal is to propose appropriate methods to simultaneously handle the following three important issues: i) lack of information -usually very few samples are available, ii) a large number of available processes for manufacturing nonwoven products, iii) inaccuracy of the predicted features.…”
Section: Introductionmentioning
confidence: 99%